Making the Misreporting Policies Less Onerous in De Minimis Cases. (Policy Papers; Policy Paper, 2006)
The Managing Director's Medium-Term Strategy referred to complex misreporting procedures for even trivial forms of misreporting and called for streamlining. This paper presents a proposal to reduce the burden of the Fund's misreporting policies in cases involving de minimis deviations from program conditions. The proposal is to consider deviations from a performance criterion or other condition to be de minimis where they are so small as to be trivial with no impact on the assessment of program performance.